3t+4=500+t

Simple and best practice solution for 3t+4=500+t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3t+4=500+t equation:


Simplifying
3t + 4 = 500 + t

Reorder the terms:
4 + 3t = 500 + t

Solving
4 + 3t = 500 + t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-1t' to each side of the equation.
4 + 3t + -1t = 500 + t + -1t

Combine like terms: 3t + -1t = 2t
4 + 2t = 500 + t + -1t

Combine like terms: t + -1t = 0
4 + 2t = 500 + 0
4 + 2t = 500

Add '-4' to each side of the equation.
4 + -4 + 2t = 500 + -4

Combine like terms: 4 + -4 = 0
0 + 2t = 500 + -4
2t = 500 + -4

Combine like terms: 500 + -4 = 496
2t = 496

Divide each side by '2'.
t = 248

Simplifying
t = 248

See similar equations:

| 4(x-5)=12+x+x | | -4(x-6)-7=39 | | 16=4w+2w?2 | | -6(1+7n)=-132 | | 9/11=a | | 2x+7y=1000 | | 5(x-6)+9=43 | | -2f/3=2 | | 5(6-8x)=-130 | | -3(x-7)=17 | | 2y-5=y-2 | | 2/7=r | | 14x+70=7 | | 2(x+11)=54 | | (x^3)+(5x^2)-9x-45=0 | | 3b=-9 | | 3000-120x=15000 | | 93-(4m-8)=53 | | 2(3c)=36 | | f=(12)60-2/3r | | X*2+x*2=-14-3 | | -200x-2500=5100 | | -124=-4v-2(6+6v) | | -4x-18=73 | | y=x/2-13^3 | | 5-w+11=51 | | 7+7(7n-8)=98 | | 6x-(3x+7)=27 | | 2x+29=300 | | 6n^2+48n+72=0 | | 28n^2=-96-183n | | 5a+56=(7)(8) |

Equations solver categories